Ndau identity in the Mozambique-Zimbabwe borderland - Patrício, Marta (2011)
The Ndau are one of many African groups that show the division provoked by the establishment of colonial borders. The effects caused by this territorial demarcation to the definition of a transnational Ndau identity, as well as the evolutions around this identitarian feeling, specially affected by sociopolitical transformations in both countries (specially colonial wars and civil wars) are fundamental analysis elements to the update of knowledge about this ethnic group. The academic debates about ethnicity have been largely discussed in the past decades, specially the ethnicity historicity, i.e., if ethnic groups are deep-rooted in ancestral identities or if they were invented by colonialism. Jean-Loup Amselle, for instance, sustains that ethnic identities are colonial creations, that there wasn’t such thing as an ethnic group during pre-colonial ages and that ethnic identities were sculpted only by the colonizers’ will of territorialize the African continent; after that, the local populations have reappropriated these identities. However, nowadays there is an emerging consensus about the importance of looking to ethnic identities as a process of constant transformations, adaptations and negotiations previous to colonialism (although only known in this period), more than looking for exact moments of crucial construction or rupture.